Local Currency Bond Markets : A Diagnostic Framework. (Policy Papers; Policy Paper ;, 2013)
In November 2011, the G-20 endorsed an action plan to support the development of local currency bond markets (LCBM). International institutions-the IMF, the World Bank, the EBRD, and the OECD-were asked to draw on their experience to develop a diagnostic framework (DF) to identify general preconditions, key components, and constraints for successful LCBM development. The objective is to provide a tool for analyzing the state of development and efficiency of local currency bond markets. The application of the DF is expected to be flexible, bearing in mind that the potential for LCBM development depends on economic size, financing needs, and stage of economic development.